Analisis Tingkat Pendidikan dengan Pengetahuan dan Sikap tentang Kesehatan Reproduksi Calon Pengantin di Puskesmas Sawah Besar Periode November-Desember 2021 - Johara Johara (Jurnal Riset Hesti Medan, 2022)
Reproductive health is currently the target of the 3rd goal of a sustainable society (SDG) and the 5th goal of SDG. Therefore, it is important to maintain reproductive health in an effort to realize people's welfare, but what happens is that there are still problems that are analyzed with reproductive health, especially in developing countries. Maternal mortality rate (MMR) is a sensitive indicator to describe the welfare of society in a country. This study uses a descriptive method that aims to make an objective analysis of a situation regarding the knowledge of the prospective bride and groom about reproductive health. The design of this study was through a cross-sectional quantitative approach by measuring or observing at the same time, and collecting data using a questionnaire. Based on the results of univariate research, it was found that the educational level of the prospective bride and groom with university education was 6 people (20,0%), high school, junior high school education levels, 22 people (73,3%) elementary school education level, 2 people (6,7%). Most of the prospective bride and groom had good knowledge of 7 people (23,3%), 17 people (56,7%) had sufficient knowledge, 6 people (20,0%) had less knowledge. Most of the prospective bride and groom with an attitude of Strongly Agree as many as 9 people (30,0%), Agree attitude as many as 14 people (46,7%), Disagree attitude 4 people (13.3%) and Strongly Disagree 3 people (10,0%). Most of the respondents had sufficient knowledge about reproductive health for prospective brides at the Sawah Besar District Health Center for the November-December 2021 period.